Analisis Penerapan Anggaran Kinerja Pada Dinas Lingkungan Hidup Kota Magelang - Devi Ashari; Tasyanari Handayani; Wahyu Marginingtyas Andika Putri; Afina Khusna Mufidah; Mia Nurmalia; Herlina Manurung (Jurnal Akuntan Publik, 2024)
The study aims to analyze the implementation of performance-based budgets available at the City of Magelang Environmental Services. Data gathering was conducted with the Technical interview to the Chief of Combat Fields. The results of this study identified the process of planning the maintenance of the livelihood of the city of Magelang, the implementation of performance-based maintenance on the city's livelihoods, the weaknesses of the execution of the performance-driven budget on the performance of the activities on the lively life of the town of Magalang, and the improvement of the application of the performing-based management of the life of a city of Magelang.